A comprehensive service delivery model for preschoolers with special educational needs: Its characteristics and effectiveness. (February 2019) - Lam, Shui-fong; Tsang, Nancy; Keung, Yuen-Ching; Tong, Ying; Mok, Flora; Chiu, Amy; Lai, Yvonne; Yuen, Lily; Soh, Desmond
Abstract: Background: The compartmentalization between early intervention services and early childhood special education programs is a worldwide phenomenon, which results in the fragmentation of services for preschoolers with special educational needs (SEN). Aims: To address this fragmentation of services, an intervention program in Hong Kong adopted a comprehensive service delivery model with six characteristics: 1) multidisciplinary approach, 2) integration of services across different contexts, 3) multimodal intervention with direct and indirect services, 4) capacity building for systems, 5) inclusive environment, and 6) high program intensity. Methods: The program evaluation was a quasi-experiment with a control group (n = 60) matched to the experimental group (n = 60). Results: At the end of the school year, the experimental group made significant improvement in most measures including cognitive skills, receptive language skills, expressive language skills, gross-motor skills, fine-motor skills, and self-direction skills. School heads in the experimental group also agreed that the program had empowered their teachers and reinforced their school systems. Conclusion: Despite its exploratory nature, the study has shed light on the future directions of services for preschoolers with SEN. The comprehensive service delivery model offers a response to the fragmentation of services and reveals the importance of integration of services across different contexts with multidisciplinary approach.